Theory for composite sandwich structures with unsymmetrical wythes and transverse interaction. (1st June 2016) - Bai, Fengtao; Davidson, James S.
Highlights: Governing equations of both longitudinal and transverse interactions for unsymmetrical wythes sandwich structures are derived. Transverse interaction is decoupled from longitudinal interaction and theoretically studied. Closed form solutions of all the governing equations are provided. Newly presented theoretical development shows significant improvement in the accuracy. Abstract: Although concrete sandwich structures, such as the wide variety of insulated wall panels in use today, have gained increasing popularity over recent years, a rigorous analytical approach that captures and defines its complicated mechanics is lacking. This work addresses that concern by deriving a general form of governing equations for unsymmetrical wythe sandwich structures that includes both longitudinal and transverse interactions. A decoupled analysis procedure based on those governing equations that is applicable for design use is then presented. Finally, mathematical proof that demonstrates the difference and relationships between this newly developed methodology and popular existing theories is presented, and discussion of the implications and importance of the approach is provided.